Construction Time-Cost Optimization Modeling Using Ant Colony Optimization - Mohammed Nooruldeen Azeez; Angham Alsaffar (Journal of Engineering, 2023)
In the field of construction project management, time and cost are the most important factors to be considered in planning every project, and their relationship is complex. The total cost for each project is the sum of the direct and indirect cost. Direct cost commonly represents labor, materials, equipment, etc. Indirect cost generally represents overhead cost such as supervision, administration, consultants, and interests. Direct cost grows at an increasing rate as the project time is reduced from its original planned time. However, indirect cost continues for the life of the project and any reduction in project time means a reduction in indirect cost. Therefore, there is a trade-off between the time and cost for completing construction activities. In this research, modeling of time-cost optimization, generating global optimum solution for time and cost problem, and lowering construction time and cost using ant colony optimization algorithm